Moderate Alcohol Intake Changes Visual Perception by Enhancing V1 Inhibitory Surround Interactions - Wang, Huan; Wang, Zhengchun; Zhou, Yifeng; Tzvetanov, Tzvetomir (Frontiers in Neuroscience, 2021)
Moderate alcohol consumption is considered to enhance the cortical GABA-ergic inhibitory system and it also variously affects visual perception. However, little behavioral evidence indicates changes of visual perception due to V1 modulated by alcohol intoxication. In this study, we investigated this issue by using center-surround tilt illusion (TI) as a probe of V1 inhibitory interactions, by taking into account possible higher-order effects. Participants conducted TI measures under sober, moderate alcohol intoxication and placebo states. We found alcohol significantly increased repulsive TI effect and weakened orientation discrimination performance, which is consistent with the increase of lateral inhibition between orientation sensitive V1 neurons caused by alcohol intoxication. We also observed no visible changes in the data for global orientation processing but a presence of global attentional modulation. Thus, our results provide psychophysics evidences that alcohol changed V1 processing that affects visual perception of contextual stimuli.